2004
DOI: 10.7326/0003-4819-140-12-200406150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Physical Exercise on Inflammation and Atherosclerosis in Men: The DNASCO Study

Abstract: Aerobic physical exercise did not attenuate progression of atherosclerosis, except in a subgroup of men not taking statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 31 publications
5
104
1
6
Order By: Relevance
“…18 Certified sonographers measured carotid IMT, the subject being in the supine position, with the head turned 451 from the side being scanned. An ultrasound device with a high-resolution 10-MHz transducer was used following a standardized and pretested protocol.…”
Section: Methodsmentioning
confidence: 99%
“…18 Certified sonographers measured carotid IMT, the subject being in the supine position, with the head turned 451 from the side being scanned. An ultrasound device with a high-resolution 10-MHz transducer was used following a standardized and pretested protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Since the population studied consists of well doing subjects, the obtained findings may not be applied to general population or physically inactive subjects. A recent randomized controlled intervention trial shows that aerobic physical exercise has no effects on progression of atherosclerosis in middle-aged white men 27) . Since exercise is known to increase anaerobic threshold 28) , the threshold may be elevated in a physically active population such as SDFs personnel.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that exercise-induced EPC mobilization enhances vascular repair. Exercise may also halt atherosclerotic disease progression as ascertained in both the coronary and carotid beds (Belardinelli, Paolini et al 2001;Hambrecht, Walther et al 2004;Rauramaa, Halonen et al 2004). While multiple studies have shown exercise to mobilize EPCs, the total amount of physical activity has been associated directly with EPC numbers which is consistent with a dose-response (Adams, Lenk et al 2004;Sandri, Adams et al 2005;Luk, Dai et al 2009).…”
Section: Physical Activitymentioning
confidence: 57%